How do you simplify 2x−4x+2? Algebra Expressions, Equations, and Functions Variable Expressions 1 Answer Olivier B. Oct 1, 2015 2x−4x+2=2(1−x) Explanation: 2x−4x+2=(2x−4x)+2=−2x+2=2⋅(−x)+2⋅1=2(−x+1)=2(1−x) Answer link Related questions How do you write the variable expression for: a quotient of 2 and the sum of a number and 3 ? What are variables? What are variable expressions? How do you write variable expressions? How do you evaluate variable expressions? How do you simplify the expression 3x−x+4? How do you write a quotient of a number and 6 as an expression? How do you evaluate the expression 2x+1 for x=1? How do you write a product of a number and 2 as an expression? How do you write 5 less than 2 times a number as a variable expression? See all questions in Variable Expressions Impact of this question 2280 views around the world You can reuse this answer Creative Commons License